Alkali Halide Aqueous Solutions Under Pressure: A Non-Equilibrium Molecular Dynamics Investigation of Thermal Transport and Thermodiffusion - Guansen Zhao; Fernando Bresme (Entropy)
Thermal gradients induce thermodiffusion in aqueous solutions, a non-equilibrium effect arising from the coupling of thermal and mass fluxes. While thermal transport processes have garnered significant attention under standard conditions, thermal transport at high pressures and temperatures, typical of the Earth’s crust, has escaped scrutiny. Non-equilibrium thermodynamics theory and non-equilibrium molecular dynamics simulations provide an excellent means to quantify thermal transport under extreme conditions and establish a connection between the behaviour of the solutions and their microscopic structure. Here, we investigate the thermal conductivity and thermal diffusion of NaCl and LiCl solutions in the GPa pressure regime, targeting temperatures between 300 K and 1000 K at 1 molal concentration. We employ non-equilibrium molecular dynamics simulations along with the Madrid-2019 and TIP4P/2005 force fields. The thermal conductivity of the solutions increases significantly with pressure, and following the behaviour observed at standard pressure, the thermal conductivity is lower than that of pure water. The reduction in thermal conductivity is significant in the GPa pressure regime, ∼3% for 1 molal NaCl and LiCl solutions. We demonstrate that under GPa pressure conditions, the solutions feature thermophobic behaviour, with ions migrating towards colder regions. The pronounced impact of pressure is more evident in LiCl solutions, which display a thermophilic to thermophobic “transition” at pressures above 0.25 GPa. We discuss a correlation between the solution’s thermophobicity and the disruption of the water hydrogen bond structure at high pressure, where the water structure resembles that observed in simple liquids.